2010
DOI: 10.1371/journal.pone.0015522
|View full text |Cite
|
Sign up to set email alerts
|

CpG Demethylation Enhances Alpha-Synuclein Expression and Affects the Pathogenesis of Parkinson's Disease

Abstract: BackgroundAlpha-synuclein (SNCA) gene expression is an important factor in the pathogenesis of Parkinson's disease (PD). Gene multiplication can cause inherited PD, and promoter polymorphisms that increase SNCA expression are associated with sporadic PD. CpG methylation in the promoter region may also influence SNCA expression.Methodology/Principal FindingsBy using cultured cells, we identified a region of the SNCA CpG island in which the methylation status altered along with increased SNCA expression. Postmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
220
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(237 citation statements)
references
References 40 publications
7
220
2
4
Order By: Relevance
“…It is well known that mutation and expression levels of this gene are associated with PD [ 77 ]; interestingly, SNCA promoter was found to be significantly demethylated in the cortex, substantia nigra and putamen obtained from patients affected by the sporadic form of PD, stressing that DNA hypomethylation could be causative for SNCA overexpression in the disease [ 78 ]. It was also shown that the hypomethylation of a specific CpG-rich region was characteristic of specific brain areas from subjects with sporadic PD, pointing to the concept that different brain areas show differential susceptibility to gene-specific methylation in PD and maybe in other neurodegenerative diseases [ 79 ]. Finally, a genome-wide association meta-analysis evidenced that other loci associated to PD risk (PARK16, GPNMB, and STX1B) are characterized by differential expression and DNA methylation in cortex and cerebellum [ 80 ].…”
Section: Dna Methylation and Neurodegenerationmentioning
confidence: 97%
“…It is well known that mutation and expression levels of this gene are associated with PD [ 77 ]; interestingly, SNCA promoter was found to be significantly demethylated in the cortex, substantia nigra and putamen obtained from patients affected by the sporadic form of PD, stressing that DNA hypomethylation could be causative for SNCA overexpression in the disease [ 78 ]. It was also shown that the hypomethylation of a specific CpG-rich region was characteristic of specific brain areas from subjects with sporadic PD, pointing to the concept that different brain areas show differential susceptibility to gene-specific methylation in PD and maybe in other neurodegenerative diseases [ 79 ]. Finally, a genome-wide association meta-analysis evidenced that other loci associated to PD risk (PARK16, GPNMB, and STX1B) are characterized by differential expression and DNA methylation in cortex and cerebellum [ 80 ].…”
Section: Dna Methylation and Neurodegenerationmentioning
confidence: 97%
“…A number of recent studies have shown that the expression level of the gene encoding α-syn is regulated through epigenetic mechanisms, through a methylated CpG in intron 1 and through HDAC activity (Du et al, 2010;Jowaed et al, 2010;Matsumoto et al, 2010) (Fig. 5A).…”
Section: Epigenetic Control Of and By α-Synucleinmentioning
confidence: 99%
“…Although the role of DNA methylation and its link to PD pathogenesis is currently unclear, methylation of the SNCA gene may be involved in pathology via structural changes or the overexpression of the protein, leading to protein aggregation, or via impaired gene expression. Methylation of SNCA intron 1 has been demonstrated to be associated with decreased SNCA transcription, whereas reduced methylation at this site was found to be decreased in several brain regions, including the substantia nigra, of sporadic PD patients, causing the increased expression of the SNCA gene [23,24]. These results raise the possibility that the increased α-synuclein production that is associated with PD may result from increased SNCA expression, as a consequence of a decreased methylation state of the SNCA gene.…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 92%